Soil physicochemical properties and microbial biomass in agriculture and abandoned lands of Shivapuri-Nagarjun National Park, Kathmandu, Nepal - Til Maya Dhakal; Lal Bahadur Thapa; Nikolaos Monokrousos; Ram Kailash Prasad Yadav; Chandra Prasad Pokhrel (Universitas Sebelas Maret, 2026)
Evaluating soil physicochemical and biological properties helps to understand ecosystem functions and nutrient dynamics. This study assessed the physicochemical and microbial properties of soil in agricultural and abandoned lands within Shivpuri-Nagarjun National Park, Nepal. Soil samples were collected from both agriculture and abandoned lands at soil depths of 10 to30 cm during the pre-monsoon, monsoon, and post-monsoon seasons. Physicochemical parameters of the soil were analyzed by using standard protocols. The chloroform fumigation extraction method was applied for determination of microbial biomass carbon and nitrogen. Soil temperature decreased with increasing depth during both pre-monsoon and monsoon seasons, but it was increased on increasing the depth during post-monsoon. Agricultural land exhibited higher proportions of silt and clay, whereas abandoned land was characterized by a higher sand content. In agricultural soils, soil organic carbon was 2.63%, total nitrogen and available phosphorus were 0.21% and 72.16 kg ha-1, respectively, while available potassium was 636.55 kg ha-1. These nutrient levels peaked during the monsoon season and declined with increasing soil depth. Similarly, microbial biomass carbon (465.82 μg g-1) and nitrogen (48.58 μg g-1) were also higher in agricultural land, showing an increasing trend with depth. The microbial biomass carbon-to-nitrogen ratio ranged from 9.61 to 19.41. The first (PC1) and second (PC2) components of Principal Component Analysis (PCA) accounted for 35.5% and 12.4% of the total variance, respectively. Overall, agricultural land, upper soil layers, and the monsoon season were identified as the most influential factors contributing to improved soil characteristics.